0041 Associations of thermophilic actinomycetes and non-tuberculous mycobacteria with respiratory health in occupants of a water-damaged office building. (23rd June 2014) - Park, Ju-Hyeong; Cox-Ganser, Jean; White, Sandra; Laney, Scott; Caulfield, Steve; Turner, William; Sumner, Austin; Kreiss, Kathleen
Abstract : Objectives: We examined microbial correlates of health outcomes in employees in a building with a sarcoidosis cluster and excess asthma. Method: We offered employees a questionnaire and pulmonary function tests (PFT) and collected 120 floor dust samples by vacuuming workstation areas or the exterior rim of the floor. We analysed dust for culturable fungi, bacteria, actinomycetes, non-tuberculous mycobacteria, and cell wall components of fungi [(1→3)-β-D-glucan] and Gram-negative bacteria (endotoxin). Results: Among 136 employees, 77% participated in the questionnaire, 64% in PFTs, and 49% in both. Of the 105 questionnaire participants, 50 (48%) reported at least one hypersensitivity pneumonitis (HP)-like symptom (shortness of breath on exertion, flu-like achiness, or fever and chills) in the last 4 weeks; 69 (66%) reported at least one HP-like symptom in the last 12 months. PFT results were abnormal or borderline for 13 participants (6 obstruction; 2 restriction; 2 mixed pattern; and 3 borderline obstruction). In multivariate logistic regressions, log-transformed levels of thermophilic actinomycetes (GM=580 CFU/m 2 ) were positively associated with HP-like symptoms in the last 4 weeks [odds ratio (OR)=1.6, 95% confidence interval (CI)=1.15–2.35] and 12 months (OR=1.6, 95% CI=1.09–2.32), and with an abnormal/borderline PFT result (OR=1.7, 95% CI=1.04–2.88). Log-transformed mycobacteria levels (GM=960 CFU/m 2 ) were marginally positively associated with HP-like symptoms in the last 4 weeks that improved when away from the building (OR=1.9; 95% CI=0.95–3.85). These associations were not confounded by smoking, gender, age, or building tenure. Conclusions: Our study suggests that thermophilic actinomycetes and non-tuberculous mycobacteria may have played a role in the respiratory illness among occupants of this water-damaged building.